RETENTION STRATEGY TO MINIMIZE NURSE TURNOVER: A SYSTEMATIC REVIEW: DOI: https://doi.org/10.35654/ijnhs.v1i2.47 - Rr.Tutik Sri Hariyati; Nurdiana Nurdiana (Alta Dharma Publisher, 2018)
Background: Communication skills are essential for nurses in providing health services. Efficacious communication will impact in the quality of care and patient safety. This manuscript is to identify factors predisposing implementation of effective nurse communication. Method: This study that data was retrieved uses systematic review design. Data was retrieved from database ProQuest, SCOPUS, EBSCO, Science-Direct, JSTOR, and Wiley-Online in the period of 2011 – 2017. The study was done for journal, article and literature review by applying the keywords nurse communication, health’s communication, effective communication of nurse. Results: A total of 12518 studies was found from six databases. From, the number of these direct search, systematic review identifies conformity based on the title, so that it obtained 31 studies with a title that suitable for a selected discussion. The total of selected papers were 16 studies and identified Efficacious communication. Analysis result from the paper research was there were 16 papers that complement the criteria determined. Six factors are identified to have effect in an implementation of effective nurse communication: (1) intelligence and self-efficacy, (2) Communication Skills, (3) Work Experience, (4) Perceptions, (5) Socio-cultural, and (6) Organization culture.